2016
DOI: 10.4049/jimmunol.1502122
|View full text |Cite
|
Sign up to set email alerts
|

The C-Terminal Acidic Region of Calreticulin Mediates Phosphatidylserine Binding and Apoptotic Cell Phagocytosis

Abstract: Calreticulin is a calcium-binding chaperone that is normally localized in the endoplasmic reticulum (ER). Calreticulin is detectable on the surface of apoptotic cell under some apoptosis-inducing conditions, where it promotes phagocytosis and immunogenicity of dying cells. However, the precise mechanism by which calreticulin, a soluble protein, localizes to the outer surface of the plasma membrane of dying cells is unknown, as are the molecular mechanisms that are relevant to calreticulin-induced cellular phag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
32
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(34 citation statements)
references
References 49 publications
2
32
0
Order By: Relevance
“…Consistent with this idea HMGB1 can inhibit PS‐mediated efferocytosis in apoptotic neutrophils . Whether CRT, which binds PS through its C‐terminal acidic region, also blocks PS signaling awaits further investigation. Similarly, studies combining ICD inducers with PS targeting antibodies or AnxV might also have combinatorial value to skew immune responses in favor immunogenicity.…”
Section: Tolerogenic Versus Inflammatory Cell Death Pathwaysmentioning
confidence: 61%
See 1 more Smart Citation
“…Consistent with this idea HMGB1 can inhibit PS‐mediated efferocytosis in apoptotic neutrophils . Whether CRT, which binds PS through its C‐terminal acidic region, also blocks PS signaling awaits further investigation. Similarly, studies combining ICD inducers with PS targeting antibodies or AnxV might also have combinatorial value to skew immune responses in favor immunogenicity.…”
Section: Tolerogenic Versus Inflammatory Cell Death Pathwaysmentioning
confidence: 61%
“…In addition to their role in ICD, both CRT and HMGB1 have been shown to interact with PS, and therefore it is possible that in addition to their role in inflammatory signaling, exposure of these molecules masks tolerogenic signals of PS‐mediated efferocytosis . Consistent with this idea HMGB1 can inhibit PS‐mediated efferocytosis in apoptotic neutrophils .…”
Section: Tolerogenic Versus Inflammatory Cell Death Pathwaysmentioning
confidence: 91%
“…Similar to its ER membrane homologue calnexin (CNX) ectodomain, CRT is composed of a globular domain, into which a flexible arm-like P (proline-rich) domain is inserted (Schrag et al, 2001). In addition, a highly charged and flexible C-terminus extension in CRT and CNX can bind numerous calcium ions with low affinity (Michalak et al, 2002;Wijeyesakere et al, 2016). The globular domain is made up of seven concave and six convex -sheets forming a legume lectin fold (Chouquet et al, 2011;Kozlov et al, 2010;Schrag et al, 2001).…”
Section: Introductionmentioning
confidence: 99%
“…Likewise, the highly acidic N-terminal and C-terminal regions of calnexin also contain multiple lowaffinity calcium-binding sites [44]. More recent studies demonstrated that the C terminus of calreticulin has a propensity to form a helical structure [45] and its secondary structure gets enhanced in the presence of Ca 2+ ions [45,46]. , and calreticulin 3 (CRT3).…”
Section: Structure Of Calnexin/calreticulinmentioning
confidence: 99%